Regulation of International Straits - Djalal, Hasjim (Indonesian Journal of International Law, 2009)
Generally this article discusses regulation on international strait which involves the straits of Malacca and Singapore. With regard to the straits used for international navigation, the 1982 UNCLOS prescribes the rights and obligations of the States bordering the straits as well as the users in transip passage. This article describes the problems of the straits of Malacca and Singapore which mainly lay on how to ensure safety and protect environment of the coastal States, Development od Cooperative Mechanism, bilateral cooperation, and new issues. In conclusion, the author share his lesson learned within the last decades on his experiences.